Sport-Related Portal Vein Thrombosis: An Unusual Complication - Igor Dumic; Nikola Tankosic; Milica Stojkovic Lalosevic; Tamara Alempijevic (Case Reports in Hepatology)
Portal vein thrombosis (PVT) is an uncommon condition usually associated with hypercoagulable states or liver cirrhosis. PVT due to sports-related injuries is rarely reported and, to the best of our knowledge, only two cases have been reported thus far. Brazilian jiu-jitsu (BJJ) is a form of martial arts and is considered very safe with minimal risk for injury. It has growing popularity worldwide. Here, we report the first case of PVT secondary to abdominal trauma related to the practice of (BJJ) in an otherwise healthy 32-year-old man with no other traditional risk factors for PVT.